2022
DOI: 10.1088/1361-6595/ac47e5
|View full text |Cite
|
Sign up to set email alerts
|

Axial and radial development of the hot electron distribution in a helicon plasma source, measured by a retarding field energy analyzer (RFEA)

Abstract: The information about the electron population of a helicon source plasma that expands along a magnetic nozzle is important for understanding the plasma acceleration across the potential drop that forms in the nozzle. The electrons need an energy higher than the potential drop to escape from the source. At these energies the signal of a Langmuir probe is less accurate. An inverted RFEA measures the high-energy tail of the electrons. To reach the probe, they must have energies above the plasma potential VP, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Numerous experiments and simulations have reported the formation of a hollow density structure, also called highdensity conics, in the diffusion region of an RF plasma expanding in a symmetric magnetic nozzle [13][14][15][16][17][18][19][20][21][22][23][24]. A common feature in the literature is the concomitance of the conics with the most radial streamlines leaving the source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experiments and simulations have reported the formation of a hollow density structure, also called highdensity conics, in the diffusion region of an RF plasma expanding in a symmetric magnetic nozzle [13][14][15][16][17][18][19][20][21][22][23][24]. A common feature in the literature is the concomitance of the conics with the most radial streamlines leaving the source.…”
Section: Introductionmentioning
confidence: 99%
“…A common feature in the literature is the concomitance of the conics with the most radial streamlines leaving the source. The generation of these high-density conics has been attributed to highenergy electrons created a few skin depths under the antenna that escape the plasma source along the last radial field lines leaving the glass tube and causing off-axis local ionisation [15,16,19,22,24,25]. Takahashi et al [16] have shown the presence of a high electron temperature region all along the field lines which intersect the antenna and can expand downstream.…”
Section: Introductionmentioning
confidence: 99%